Zentra: Meja Belajar Pintar Portabel Berbasis Iot Untuk Gen Z - Fauhad Ziyad Fakhruddin; Galih Setyawan (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2025)
The advancement of technology has significantly influenced future generations, including Generation Z. This generation is highly dependent on technology, especially in learning activities. However, learning effectiveness is often disrupted by environmental factors such as room temperature, poor lighting, and back pain due to prolonged static sitting posture. This research aims to design a portable smart study desk based on the Internet of Things to improve learning comfort and productivity. The system is developed using an ESP32 microcontroller connected to several sensors. The FSR402 sensor detects arm pressure as an indicator of sitting posture, the DHT22 monitors temperature and humidity, and the LDR senses ambient lighting. Additionally, the desk is equipped with a cooling fan controllable via smartphone. Sensor data is transmitted in real-time to the Blynk platform and supported by a notification system to alert the user. Accuracy testing was conducted using reference tools such as a thermohygrometer and a luxmeter, along with evaluating the effectiveness of the laptop cooling feature. The results show that the system can provide accurate environmental data and support more productive and effective study sessions. These findings highlight the potential for further development of adaptive IoT-based learning tools tailored to modern user needs.